The relationship between language proficiency and use of collocation by Iranian EFL students - Firooz Namvar, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
An increased knowledge of collocation not only allows learners to improve levels of accuracy, but it also aids fluency (Webb & Kagimoto 2011). Collocations improve the learner's ability in oral communication, listening, and reading skills. From the perspective of pedagogy collocations help learners to be aware of language chunks used by native speakers in writing and speaking. This study investigated learners’ use of collocations by analyzing the learners’ written work based on multiple choice tests and a writing task. Fifteen Iranian postgraduate students participated in this study to determine the collocational errors they made and to identify the basis for their difficulty with collocations. The results showed that learners had problem with both lexical and grammatical collocations in their writing because the language transfer appeared to have a strong effect on the participants’ production of collocation. In addition, the findings indicated that the use of collocations is related to proficiency in English and there is a strong relationship between knowledge of collocations and the overall proficiency